Poetry of wine in Ibn Zaidoun's Andalusian Diwan: An objective analytical study - Al-Khatatneh, Hamzah Abed-Alsalam (Arab Journal for Sciences and Research Publishing, 2021)
This study aims at exploring a very important aspect of the most prominent life rituals that the Andalusian poet Ibn Zaydun lived during his compilation of the poems of the wine. They formed in his collection a symbol of deep artistic significance, reflecting the images of himself and his emotions in their furthest limits. Therefore, his literary work was fertile. This came up with his description of the psychological state that dominated him in the various fields in which he narrated the poems of wine, such as love, smiling nature, captivity and praise. All this raised up the faculty of poetry in Ibn Zaydun, making the rituals of drinking wine a distinguished world for him. In the introduction to the study I dealt with introducing Ibn Zaidoun and the influence of the Andalusian nature on him in the systems of the most beautiful poems and poems, and in other studies of the study that included describing the wine, describing its drinkers and drinking boards, and I tried in this study to reveal the close relationship between wine and spinning poetry, and to clarify the role of wine In influencing the psychological state of Ibn Zaidoun.
Keywords: Andalusian Poetry; Wine Poetry; The Collected Poems of Ibn Zaydun